1. Engineering
  2. Computer Science
  3. prove through math induction a0 a1 a2 ...

Question: prove through math induction a0 a1 a2 ...

Question details

Prove through math induction:

a^0 + a^1 + a^2 + .... + a^n= (1-(a^n+1))/(1-a)

The first expression, using a = 2 and n = 4, would be:

20+21+22+23+24 = 1+2+4+8+16 = 31

The second expression, using a = 2 and n = 4, would be:

(1-24+1)/(1-2) = (1-25)/-1 = (1-32)/-1 = -31/-1 = 31

a) What is your hypotheses for using the induction step

b) Complete the induction steps

Solution by an expert tutor
Blurred Solution
This question has been solved
Subscribe to see this solution